Relationship between Patients’ Knowledge and Medication Adherence of Tuberculosis at Islamic Hospital Pondok Kopi Jakarta - Maifitrianti, Maifitrianti; Wiyati, Tuti; Hasanah, Nur (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: Tuberculosis (TB) remains a health problem in Indonesia. Currently, the number of new TB cases in Indonesia ranks second after India. Patient compliance in using antituberculosis drugs is critical in achieving successful treatment outcomes, prevent further spread of the bacteria that cause TB and the development of drug resistance. Adherence to taking medication can be influenced by various factors, one of which is the level of knowledge.Objectives: This study was aimed to determine the relationship between the level of knowledge about TB and medication adherence of TB patients at the Jakarta Islamic Hospital Pondok Kopi.Methods: This study was conducted from May to June 2022 with a cross sectional design.  The inclusion criteria in this study were TB patients who were over 18 years old, willing to become respondents, and had used antituberculosis drugs for at least one month. The level of knowledge about TB was assessed using a questionnaire and medication adherence was assessed using the MARS-5 questionnaire.Results: The number of respondents in this study was 83 patients. Most patients were male (57.83%), less than 60 years old (83.13%), and had a high school education (53.01%). The results showed that most patients (73.47%) had a good level of knowledge and were compliant with taking medication (77.11%). The level of patient knowledge about TB has a significantly moderate and positive correlation with the level of adherence in taking medication (p 0.001; r 0.517).Conclusion: increasing patients’ knowledge about TB can lead to better patients’ adherence, which may lead to better treatment outcome.